Analisis Tingkat Kecerahan Langit Malam Terhadap Visibilitas Hilal Menggunakan Sky Quality Meter di Observatorium Malikussaleh IAIN Lhokseumawe - Devina Kharida Alhan; Ruslandi Ruslandi; Ismail Ismail (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
In the dark of the night, the sky offers wonders like the crescent moon (hilal), which marks the beginning of the Islamic month. The hilal is often observed at the Malikussaleh Observatory, IAIN Lhokseumawe. This study uses a Sky Quality Meter (SQM) to measure the night sky brightness and how it affects hilal visibility. This field research employs a qualitative approach with a descriptive method. Primary data is obtained from direct observations using the SQM before and after sunset, while secondary data comes from relevant literature. The study finds that the night sky brightness at the observatory is Class 5 on the Bortle Scale, with an average of 19.80 MPSAS, categorized as Suburban Sky. The average brightness during hilal observation is -3.03397 v mag, while the hilal magnitude is -7.36 v mag. Therefore, the hilal can be observed if its magnitude is lower than the night sky brightness.